2020
DOI: 10.3389/fpls.2020.00849
|View full text |Cite
|
Sign up to set email alerts
|

Photobleaching of Chlorophyll in Light-Harvesting Complex II Increases in Lipid Environment

Abstract: Excess light causes damage to the photosynthetic apparatus of plants and algae primarily via reactive oxygen species. Singlet oxygen can be formed by interaction of chlorophyll (Chl) triplet states, especially in the Photosystem II reaction center, with oxygen. Whether Chls in the light-harvesting antenna complexes play direct role in oxidative photodamage is less clear. In this work, light-induced photobleaching of Chls in the major trimeric light-harvesting complex II (LHCII) is investigated in different mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 90 publications
1
28
0
Order By: Relevance
“…The fact that the formation of the quenching site within the core of PSII precedes D1 cleavage leaves several options regarding the quenching mechanism, including non-photochemical energy dissipation and charge separation-based quenching. It was recently shown that protein oxidation events take place early upon photoinhibition (Kale et al, 2017) and that they can induce quenching in pigment-protein complexes (Lingvay et al, 2020); furthermore, it was observed that oxygen influences the F M level during photoinhibition (Gong and Ohad, 1991). We thus investigated whether oxygen is necessary for (1) the quenching itself, or (2) for the formation of the q I site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the formation of the quenching site within the core of PSII precedes D1 cleavage leaves several options regarding the quenching mechanism, including non-photochemical energy dissipation and charge separation-based quenching. It was recently shown that protein oxidation events take place early upon photoinhibition (Kale et al, 2017) and that they can induce quenching in pigment-protein complexes (Lingvay et al, 2020); furthermore, it was observed that oxygen influences the F M level during photoinhibition (Gong and Ohad, 1991). We thus investigated whether oxygen is necessary for (1) the quenching itself, or (2) for the formation of the q I site.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of 1 O 2 is well established upon photoinhibition and ROS have been shown to damage the protein scaffold (Kale et al, 2017). Pigment oxidation also results in a shortening of chlorophyll excited state lifetime (Lingvay et al, 2020). Finally, singlet oxygen concentration increases linearly with light intensity, as does the rate of q I formation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RSC Chemical Biology in reconstituted membrane of pigment of light harvesting complex II from pea (Pisum sativum). 75 Spin traps Tiron (4,5-dihydroxy-1,3-benzenedisulfonic acid) and 4-POBN (a-(4-pyridyl-1-oxide)-N-tert-butylnitrone, Fig. 3B) have been used for O 2 À and OH detection respectively, in microsomal and thylakoid membranes, roots, and plant cell suspension culture.…”
Section: Reviewmentioning
confidence: 99%
“…DMPO has been successfully used to detect 1 O 2 production from extracted thylakoids 73 of spinach and derivatives of DMPO have been successfully implemented in plant tissues: DEPMPO, a phosphorylated analogue, forms a stable abduct with ˙OH in the apoplastic fluid of Zea mays roots, 74 while TEMPD (2,2,6,6-tetramethyl-4-piperidone monohydrate) forms an adduct with 1 O 2 to form paramagnetic 4-oxo-TEMPO and has been used to follow light induced 1 O 2 production in reconstituted membrane of pigment of light harvesting complex II from pea ( Pisum sativum ). 75 …”
Section: Direct Measurement Of Ros Species Using Chemical Probes Biosensors and Electron Paramagnetic Resonancementioning
confidence: 99%
“…The most lightsensitive site in the photosynthetic apparatus is the PSII complex in which electron transport activity is impaired and the D1 (and D2) reaction centre protein is degraded, see (Aro et al 1993). In addition to PSII, PSI (Sonoike and Terashima 1994;Sonoike et al 1995;Suorsa et al 2012;Tiwari et al 2016;Lima-Melo et al 2019), as well as the Chl containing light harvesting antenna structures can also be damaged by light (Zolla and Rinalducci 2002;Rinalducci et al 2004Rinalducci et al , 2008Lingvay et al 2020). The detrimental effects of light linearly depend on light intensity (Tyystjarvi and Aro 1996) and can occur at all light intensities (Keren et al 1997;Kou et al 2012), therefore plants have evolved a protective repair mechanism, by which light induced loss of photosynthetic activity can be restored.…”
Section: Introductionmentioning
confidence: 99%